Decision Analysis of Reorientation Business Strategy Through Corporate Restructuring to Secure Profit Sustainability ( Case Study PT Alam Karya Unggul Tbk) - Sembiring, Christian Valentino; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2014)
Abstract - PT Alam Karya Unggul Tbk at first is the company that operates in manufacturing especially plastics and packaging, because of the higher probability of bankruptcy becomes a major problem, in 2013 the company decided to change its core business to coal mine, acquiring Borneo Mining Contractor as a subsidiary. Changing core business ("Business Reorientation" strategy) to coal mining is one of the company rescue effort. However, the directors are still not sure whether the steps taken by them could rescue the company from bankruptcy and make the company profit sustainability. After analyzing the level of bankruptcy using the Altman Z Score, Springate S Score and Zmijewski X Score, can be concluded that the level probability of bankruptcy of the company is very high. Since company produce pp cups and galons also moving show that bankruptcy rate is very high. Board of directors provides four alternative strategies to save and make company profit sustainability. The four strategies are (i) "Company Refinancing" by producing pp cups and galons, (ii) "Product Diversification" by diversifying the product, (iii) "Business reorientation" to continue in coal mining and (iv) "Selling company "to sell the company and bought government bonds with period of 10 years.After performing the analysis using each strategy using projection and same method, generate parameters (i) Net Present Value (NPV), (ii) Internal Rate of Return (IRR), (iii) Payback Period (PP), (iv) Return on Investment (ROI) and (v) Return on Assets (ROA). But the success criteria of profit sustainability only Net Present Value (NPV) from each strategy. After the projection of each strategy, it concluded that "Product Diversification" strategy generates the greatest NPV with value of Rp. 21,238,970,000. For the implementation plan, PT Alam Karya Unggul Tbk must perform Preparation Phase, Pre-Construction Phase and Production Phase to build a factory and doing production.Keywords: reorientation business strategy, financial distress, profitability, product diversification, feasibility study